The Role of Sociodrama Learning Method as an Effort to Increase the Sense of Love for the Country in History Subjects - Aldi Cahya Maulidan (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This research is motivated by the fact that history is often considered boring and uninteresting for students because they study the past, whereas learning history is an effort to instil patriotism values and a sense of nationalism. However, by applying the sociodrama method, it allows students to connect historical events with current conditions. This research uses case study qualitative method. The case study qualitative research method is an approach used to investigate and understand certain phenomena or events in depth in the context of real life. Case study research starts from sampling with purposive sampling. Data were collected through observation, interviews, and documentation. The analysis was conducted in three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of the research at SHS (Senior High School) No. 16 in Bandung City, the use of sociodrama method enables students to better understand the historical events that have shaped the identity of the Indonesian nation. By portraying important figures or reconstructing crucial moments in Indonesian history, sociodrama method encourages learners' active participation in the learning process. As a result, the learning experience becomes deeper and more meaningful, making it easier for learners to connect past events with the context of their current lives. Therefore, it can be concluded that sociodrama method is effective in developing learners' analytical skills and critical thinking towards historical events. As a result, learners' understanding of the values of nationalism and patriotism improved.